Global citizenship, ecomedia and English language education - Römhild, Ricardo (Palgrave Macmillan, 2023)
"This book presents a unique framework for the inclusion of ecomedia in the English language classroom to help learners cultivate global citizenship. Foregrounding learner agency in a world at risk, the author proposes a framework that hinges on human rights and critical eco-cosmopolitanism to help learners position themselves in discourses on climate change and act for transformation. The book discusses eco-documentaries as multimodal, factional texts against the background of cutting-edge research, refuting a definition based on the binary of fiction and non-fiction. Translating the insights gained from this discussion to the language education context, learners are conceptualised as active designers of meaning making when engaged with eco-documentaries. Based on this discussion, the book puts forth an innovative, multiliteracies-informed concept which is embedded in a sustainability-oriented pedagogy of hope, which encourages learners to learn and practice languages of hope and advocacy. The book will be of interest to scholars in the fields of ecopedagogy, sustainability education, global citizenship education and cultural learning, film pedagogy and language education, as well as language educators."
Aus der Danksagung: "this book, based on a doctoral thesis submitted and accepted at the University of Münster, Germany"
Keywords: Weltbürgertum; Umweltschutz; Film; Englischunterricht; Globalisierung; Umwelterziehung; English language / Study and teaching; Teaching / Environmental aspects; Cosmopolitanism; Hochschulschrift